CHARACTERISTICS OF MOTIVATION AND ITS RELATIONSHIP TO RESILIENCE IN KAZAKHSTANI PARALYMPIC ATHLETES - Yuliya Krasmik; Tatiana Iancheva; Bolat Rahmalin (Journal of Applied Sports Sciences)
Paralympic sport enables people with disabilities to significantly develop their functional abilities, improving their opportunities for full personal development and social integration. One of the main challenges for athletes is maintaining their internal motivation for sport and withstanding the stress and difficulties throughout the preparation and competition period. The relationship between resilience and motivation in the context of Paralympic sports is paramount for this group of athletes.The aim of this study was to examine the characteristics of motivation and its relationship with resilience in Paralympic athletes. The study was conducted on the grounds of the Federation of Paralympic Sports of Kokchetav, Shymkent, Taraz. Sixty Paralympic athletes participated in the study. The methodology of the study included: 1) Methodology to study the motives for sports activity of V.I.2) Motives for Sports Activity (MSA) questionnaire by E. I. Tropnikov. А. E. Kalinin’s Motives for Motivation Test; S. Maddy, adaptation of D. А. Leontiev and E. I. Raskazova.The results revealed the motivation and resilience of Paralympic athletes, depending on gender and level of sports qualification. It was found that control and the integral indicator of resilience act as key constructs within the motivational system of Paralympic athletes.